Synthesis and Characterization of Valero and Isovalero Hydroxamic Acids and their Complexes with Zn(II) And Al(III): Synthesis of Valero and Isovalero Hydroxamic Acids (Biological Sciences - PJSIR, 2009)
Valerohydroxamic acid (VAH) and isovalerohydroxamic acid (IVAH) were synthesized and characterized by m.p. and pKa determination, IR and 1H NMR studies. The ligands were complexed with Zn2+ and Al3+ and the complexes were characterized by metal analysis, IR and conductance studies. Antimicrobial studies of all the com- pounds were carried out. The pKa of the ligands are 9.50 ± 0.01 (VAH) and 9.51± 0.01 (IVAH) at 25 °C and ionic strength is 0.1 mol/dm3, while their melting points are 77.8 °C and 76.8 °C, respectively. IR and 1H NMR data are consistent with the proposed formula. The complexes are non-electrolytes in EtOH. Coordination mode (0,0) is consis- tent with the IR data of the complexes. The compounds exhibited no significant antimicrobial activity.